Development of a methodology to assess the nutrient profile of popular UK meals. Issue 4 (28th September 2015) - Benelam, B.; Stanner, S.
Abstract: In order to characterise the nutrient profile of popular meals and to identify ways to improve this, a methodology was developed to assess the profile of meals by developing meal‐based nutritional criteria for macronutrients, fibre, salt and selected food groups and comparing this with recipe analysis of both homemade and partly pre‐made dishes (those using products such as cook‐in sauces and frozen meal components). Meals were compared with the criteria per portion and with front‐of‐pack labelling guidelines per 100 g. The results indicate that many popular UK meals, both homemade and partly pre‐made, would benefit from changes to improve their nutritional profile. Generally, the dishes made with partly pre‐made ingredients met criteria for total energy, total sugars and salt but often exceeded criteria for saturates and did not provide enough fibre or fruits and vegetables. Conversely, the comparable homemade dishes tended to meet the criteria for fibre and fruit and vegetables but were also more likely to exceed the criteria for saturates. A simple visual model, called the N utrition   C ompass, for representing key results for each dish was developed. Relatively simple changes to dishes, such as adding extra vegetables and pulses, using wholegrains or potatoes with skins, using less salt or high salt ingredients and swapping higher fat dairy and meat ingredients for lower fat versions, could make significant improvements to the nutrient profile of many popular dishes. Such changes should be communicated to consumers, both by health professionals and by the food industry, in particular via recipes provided on pack or in other media for pre‐prepared meal components.